Healthcare costs and resource utilization of patients with chronic post-traumatic stress disorder: a retrospective US claims analysis of commercially insured patients - Filip Stanicic; Vladimir Zah; Dimitrije Grbic; Debra de Angelo; Wendy Bibeau (Journal of Comparative Effectiveness Research)
Aim: Exploring the healthcare costs and resource use among privately insured US patients with posttraumatic stress disorder (PTSD). Methods: This study used Merative MarketScan data. The index date was defined as the first PTSD claim. Study period included a 1-year pre-index and 2-year post-index follow-up. Cases with only acute PTSD, cancer, or insurance gap during the study period were excluded. The PTSD with (PwC) and PTSD without comorbidities (PwoC) cohorts were defined by the presence/absence of comorbid mental health conditions (schizophrenia, bipolar and major depressive disorder). Baseline PTSD (BP) cohort included PwoC cases with only index PTSD event and without FDA-approved PTSDmedications or psychotherapy. Sub-analysis is conducted among patients with PTSD and substance/alcohol use disorder. Study cohorts were matched in a 1:1:1 ratio. Results: The matched sample included 5076 patients (1681 PwC, 1681 PwoC, 1714 BP). PwC patients had higher 2-year PTSD-related costs than PwoC and BP patients ($3762 vs $1750 and $841; all p < 0.001). The same trend was noted among all-cause and anxiety-related costs. PwC patients had higher 2-year PTSD-related inpatient and emergency department (ED) rates than PwoC (10.2% vs 1.7% and 6.8% vs 2.6%, all p < 0.001) and inpatient and outpatient rates than BP (10.2% vs 2.1% and 98.0% vs 93.1%; all p ≤ 0.004). The sub-analysis had 3776 patients (3154 PwC, 537 PwoC, 85 BP). PwC had higher 2-year PTSD-related costs than PwoC and BP ($7668 vs $2919 and $1,483; all p < 0.001). The same trend was noted in all-cause and anxiety-related costs. PwC also had higher 2-year PTSD-related inpatient and ED rates than PwoC (25.6% vs 10.4% and 12.7% vs 5.2%; all p < 0.001) and inpatient and outpatient rates than BP (25.6% vs 8.2% and 95.5% vs 84.7%; all p < 0.001). Conclusion: PTSD is associated with high healthcare costs and resource use. The highest economic burden was observed in patients with PTSD and mental health comorbidities.